UI/UX Design and Evaluation: Web Platform to Support Self-Regulated Learning with a User-Centered Design Approach - Azhar Nurulhaifa; Rizki Hikmawan (Universitas Pendidikan Mandalika, 2026)
This study aims to develop and evaluate a UI/UX design that supports the three phases of Self-Regulated Learning (SRL)—forethought, performance, and self-reflection—and to assess user satisfaction, usability, and feature suitability. The research employed a User-Centered Design (UCD) approach, involving two rounds of usability testing with ten participants. Data were collected using the Cognitive Walkthrough (CW), System Usability Scale (SUS), User Experience Questionnaire–Short (UEQ-Short), and semi-structured interviews to gather user feedback and suggestions for improvement. The collected data were analyzed using descriptive quantitative techniques. The results demonstrate consistent improvements across testing phases, with the SUS score increasing from 77.5 to 88, indicating an “excellent” level of usability. In addition, the final UEQ-Short overall score reached 2.575, which falls within the “excellent” acceptance category. This study addresses the limited availability of direct feedback during the self-reflection phase of SRL by integrating an AI-based chatbot as an adaptive reflection partner. The chatbot provides real-time metacognitive feedback, thereby enhancing learners’ reflective processes and supporting more effective self-regulated learning.